Efficacy and safety of hypoglycemic drugs in improving cognitive function in patients with Alzheimer's disease and mild cognitive impairment: A systematic review and network meta-analysis - Wang, Xin-Chen; Chu, Chen-Liang; Li, Han-Cheng; Lu, Kuan; Liu, Cheng-Jiang; Cai, Ye-Feng; Quan, Shi-Jian; Zhang, Shi-Jie (Frontiers in Neurology, 2022)
Objective:The purpose of this study was to compare the effects of oral hypoglycemic drugs(HD) on cognitive function and biomarkers of Mild cognitive impairment (MCI) and Alzheimer's disease (AD) through a network meta-analysis of randomized controlled trials (RCT). Method:We conducted systematic searches through PubMed, Medline, EMBASE, the Cochrane Library and Google Scholar database, with language restrictions of Chinese and English and no date restrictions. The network meta-analysis follows the preferred reporting items of System Evaluation and Meta-Analysis (PRISMA). The 16 studies included 3081 patients participated in the study, we selected Mini Mental State Examination (MMSE), Alzheimer's disease assessment scale cognitive subscale (ADAS-cog), Alzheimer's disease cooperative study activities of daily living subscale (ADCS-ADL) and Aß-42 as the outcome measures included in the study for analysis and comparison. Result:For MMSE, intranasal insulin 20IU(ITSN20) has significantly increased compared with placebo (SMD 1.11, 95%CI 0.87,1.35).For ADAS-COG scores, rosiglitazone 4mg(RLZ4) decreased significantly with placebo (SMD-1.40, 95% CI-2.57, -0.23). For ADCS-ADL scale score, intranasal insulin 40IU(ITSN40) was significantly higher compared with placebo (SMD 0.04, 95%CI 0.03, 0.05).For Aß-42, glucagon-like Peptide-1(GLP-1) and dipeptidyl peptidase 4 inhibitor(DPP-4) were better than placebo (SMD 3.10, 95%CI 1.24,4.96), (SMD 1.3, 95%CI 0.87,1.73). Conclusion:Different hypoglycemic drugs can improve the cognitive function of MCI and AD, and the improvement degree of different drugs was different, which may be related to the drug action mechanism, dosage and duration of medication.